First-in-Human Studies of [ 18 F] Fluorohydroxyphenethylguanidines - Raffel, David M; Jung, Yong-Woon; Koeppe, Robert A; Jang, Keun Sam; Gu, Guie; Scott, Peter J H; Murthy, Venkatesh L; Rothley, Jill; Frey, Kirk A (Circulation. Cardiovascular imaging, 2018)
Disease-induced damage to cardiac autonomic nerve populations is associated with an increased risk of sudden cardiac death. The extent of cardiac sympathetic denervation, assessed using planar scintigraphy or positron emission tomography, has been shown to predict the risk of arrhythmic events in heart failure patients staged for implantable cardioverter defibrillator therapy. The goal of this study was to perform first-in-human evaluations of 4-[ F]fluoro-meta-hydroxyphenethylguanidine and 3-[ F]fluoro-para-hydroxyphenethylguanidine, 2 new positron emission tomography radiotracers developed for quantifying regional cardiac sympathetic nerve density. Cardiac positron emission tomography studies with 4-[ F]fluoro-meta-hydroxyphenethylguanidine and 3-[ F]fluoro-para-hydroxyphenethylguanidine were performed in normal subjects (n=4 each) to assess their imaging properties and organ kinetics. Patlak graphical analysis of their myocardial kinetics was evaluated as a technique for generating nerve density metrics. Whole-body biodistribution studies (n=4 each) were acquired and used to calculate human radiation dosimetry estimates. Patlak analysis proved to be an effective approach for quantifying regional nerve density. Using 960 left ventricular volumes of interest, across-subject Patlak slopes averaged 0.107±0.010 mL/min per gram for 4-[ F]fluoro-meta-hydroxyphenethylguanidine and 0.116±0.010 mL/min per gram for 3-[ F]fluoro-para-hydroxyphenethylguanidine. Tracer uptake was highest in heart, liver, kidneys, and salivary glands. Urinary excretion was the main elimination pathway. 4-[ F]fluoro-meta-hydroxyphenethylguanidine and 3-[ F]fluoro-para-hydroxyphenethylguanidine each produce high-quality positron emission tomography images of the distribution of sympathetic nerves in human heart. Patlak analysis provides reproducible measurements of regional cardiac sympathetic nerve density at high spatial resolution. Further studies of these tracers in heart failure patients will be performed to identify the best agent for clinical development. URL: https://www.clinicaltrials.gov . Unique identifier: NCT02385877.